Value-Embedded Adaptive Digital Transformation in Islamic Boarding School Management: Integrating Tradition and Innovation in Islamic Education - Kadir, Abdul; Mubarok, Ramdanil (International journal of technology and education research, 2026)
This study aims to examine the transformation of Islamic Boarding School Management in the digital era by focusing on the integration of traditional values and technological innovation at Al-Munawwir Islamic Boarding School, South Sangatta. A qualitative field research approach was employed, utilizing in-depth interviews, observation, and documentation for data collection. Data were analyzed using the Miles and Huberman interactive model with a thematic approach. The findings reveal that digital transformation occurs in a gradual and adaptive manner, encompassing the digitalization of administration, the enhancement of technology-supported learning, and the strengthening of digital communication integrated into managerial functions. Digitalization is found to be complementary (augmentative) rather than substitutive, where technology reinforces rather than replaces traditional practices, with Islamic values such as adab (ethics), akhlaq (morality), and the authority of the kyai serving as the core guiding principles. However, the transformation process faces several challenges, including limited infrastructure, low digital literacy among human resources, and cultural resistance. This study proposes the Value-Embedded Adaptive Digital Transformation Model, which emphasizes the integration of core values, digital innovation, and adaptive management as key determinants of successful transformation. The findings contribute theoretically to the development of Islamic education management and provide practical implications for pesantren governance in the digital era.